2019
DOI: 10.1016/j.compscitech.2019.107880
|View full text |Cite
|
Sign up to set email alerts
|

Impact response of Kevlar/rubber composite

Abstract: This study aims to investigate the impact performance of composite panels consisting of plainwoven Kevlar fabric and rubber matrix. A finite element (FE) model in conjunction with experimental tests was developed to simulate the response of neat fabric and composite under impact loading. Each warp and weft yarn of fabric was individually modeled and combined with rubber matrix network to form the composite. To understand the effect of natural rubber on impact resistance of Kevlar/rubber composites, two types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…2, the elastomer is highly strain rate dependent while the material model is unable to include this effect. Nonetheless, the Mooney-Rivlin model can be employed with certain adjustment as mentioned in ref [36]. A number of primary simulations revealed that the order of strain rate was 10 3 ; therefore, curve fitting on the stress-strain diagram at the strain rate of 4000/s by least square method led to amounts of 5.6 MPa and 0.5 MPa for A and B, respectively.…”
Section: Elastomermentioning
confidence: 99%
“…2, the elastomer is highly strain rate dependent while the material model is unable to include this effect. Nonetheless, the Mooney-Rivlin model can be employed with certain adjustment as mentioned in ref [36]. A number of primary simulations revealed that the order of strain rate was 10 3 ; therefore, curve fitting on the stress-strain diagram at the strain rate of 4000/s by least square method led to amounts of 5.6 MPa and 0.5 MPa for A and B, respectively.…”
Section: Elastomermentioning
confidence: 99%
“…The bio-composite studied can be modeled numerically and can find applications in the fields of the automotive, computers, construction, household goods, etc. [3]- [5]For this purpose, the finite element method, as opposed to other numerical methods, is the most widely used method and can solve many problems in several applications [6]. It is very robust by combining the largest number of applications and transforming the boundary problem into a variational problem [6].…”
Section: Introductionmentioning
confidence: 99%
“…[3]- [5]For this purpose, the finite element method, as opposed to other numerical methods, is the most widely used method and can solve many problems in several applications [6]. It is very robust by combining the largest number of applications and transforming the boundary problem into a variational problem [6]. This method also offers a great ability to deal with non-linear problems as well as complex laws.…”
Section: Introductionmentioning
confidence: 99%
“…In several applications, the fabric is used as reinforcement within a polymer matrix to create moldable composites, 14,15 whereas in others, more flexible composites can be created by treating fabrics with additives 16 or laminating them with relatively compliant materials such as rubber. 17 The possibility of improving the mechanical properties of Kevlar fabric using different kinds of additives has been investigated previously. Aramid fabrics treated with shear thickening fluids (STF) have been shown to have improved friction between the yarns during impact.…”
Section: Introductionmentioning
confidence: 99%